Holotype female of Paraphytoseius scleroticus after 33 years: voucher photos, comments and description of a new genus (Acari: Phytoseiidae) - Vikram Prasad; Krishna Karmakar (Persian Journal of Acarology)
Paraphytoseius scleroticus (Gupta & Ray, 1981) known only from the holotype female and having some unique morphological features, was examined and photographed in the Zoological Survey of India, Kolkata, India. Voucher photos included in the present study indicate the presence of setae z2 and z4 on the dorsal shield that are serrated and much longer than in any other known species of the genus Paraphytoseius. Seta S5, unique for representing the cracentis species group Chant & McMurtry, 2003, to which P. scleroticus belongs, is clearly evident lateral to seta Z5. Lyrifissure idm5, not discussed or illustrated by Gupta & Ray (1981), is also present posteromedial to base of seta S5. As type specimens of many mites deteriorate over the years and often no longer show important morphological features, or are not available for study by acarologists, or are lost due to various reasons, taking voucher photos of the important features of type specimens, especially of soft bodied mites, is strongly suggested. These may be placed online for use by the phytoseiid taxonomists. A new genus, Paraphytoevanseius Prasad gen. nov., is described and a key for the identification of different genera of the subtribe Paraphytoseiina, including the new genus, and Paraphytoevanseius arjunae (Sadanan-dan, 2006) comb. nov. are given.